And I will praise Him a guide to personal worship in the Psalms - Allen, Ronald Barclay (Nashville, TN Thomas Nelson, 1992)
Includes bibliographical references.
Rev. ed. of: Praise! A matter of life and breath.
Keywords: Praise of God; Bible. O.T. Psalms -- criticism, interpretation, etc